RESTORAN APUNG SUNGAI KAKAP - Arief, Tazkia Maghfirah Nuraulia; Gultom, Bontor Jumaylinda BR; Khaliesh, Hamdil (JMARS: Jurnal Mosaik Arsitektur, 2024)
Sungai Kakap Village is a coastal village located at the mouth of the Kapuas River. Sungai Kakap Village offers coastal culinary delights such as seafood and coastal environments often used as photo spots for the enchanting sunrise and sunset. The potential of this coastal area is applied to the design of a floating restaurant. There are four methods used in designing the floating restaurant. Firstly, the design object is the "Sungai Kakap Floating Restaurant." Secondly, the types of data and data collection techniques used include collecting primary and secondary data through observation, documentation, interviews, and literature sources. Thirdly, there are analysis techniques, divided into technical analysis and synthesis techniques that produce conceptual conclusions from site analysis such as zoning and circulation. The fourth stage is the design stage, which is the final stage. Based on the explanation, the potential of Sungai Kakap Village can be developed into an attractive restaurant. The attraction of the restaurant lies in utilizing the coastal potential, where the potential of the coastal area is applied to the design of a floating restaurant. The applied floating concept includes the building's image as a restaurant, the building being open and environmentally friendly, and the building having outward orientation and inviting the public.